2014
DOI: 10.18553/jmcp.2014.20.10.1006
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Persistence Among Chronic Myeloid Leukemia Patients During Second-Line Tyrosine Kinase Inhibitor Treatment

Abstract: C hronic myeloid leukemia (CML) is a bone marrow and blood disorder accounting for 15% of adult leukemias. 1 CML is associated with a chromosomal abnormality where there is a translocation of chromosomes 9 and 22, which code for the BCR-ABL tyrosine kinase. The American Cancer Society estimates there will be 5,980 new cases of CML diagnosed (3,130 in men and 2,850 in women) during 2014 and 810 people will die of CML during this same time period.2 The median age at onset is 67 years, but CML occurs in all age g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 17 publications
1
45
0
Order By: Relevance
“…The criterion of gap of 60 days of supply was derived based on clinical expert opinion (e.g., a 15-30 day gap or 'treatment holiday' may be appropriate for a treatment interruption due to intolerance) and sensitivity analysis to test for the gap threshold ranging from 30 to 90 days, which showed that the gap threshold of 60 days achieved a good balance between identifying patients who did not subsequently resume index TKI (potential drug holiday) and maximizing sample size. For example, a gap of 1.5 times the days' supply of the prior prescription has been utilized to define treatment interruption/nonpersistence in CML 27 . We found that almost all patients ($90% or more) had TKI prescriptions with days' supply of 28/30 days.…”
Section: Methodsmentioning
confidence: 99%
“…The criterion of gap of 60 days of supply was derived based on clinical expert opinion (e.g., a 15-30 day gap or 'treatment holiday' may be appropriate for a treatment interruption due to intolerance) and sensitivity analysis to test for the gap threshold ranging from 30 to 90 days, which showed that the gap threshold of 60 days achieved a good balance between identifying patients who did not subsequently resume index TKI (potential drug holiday) and maximizing sample size. For example, a gap of 1.5 times the days' supply of the prior prescription has been utilized to define treatment interruption/nonpersistence in CML 27 . We found that almost all patients ($90% or more) had TKI prescriptions with days' supply of 28/30 days.…”
Section: Methodsmentioning
confidence: 99%
“…Threshold scores indicated that as much as 20.5% [42] of patients (per MEMS) and 36.1% [43] of patients (per physician report) met criteria for poor adherence at baseline assessment. At 1 year, the proportion of patients meeting criteria for poor adherence per medication possession ratio (,85%) was also high, ranging from 27.3% [41] to 40.9% [15] across studies.…”
Section: Rates Of Adherence To Oral Antineoplastic Therapiesmentioning
confidence: 99%
“…Also shown in Table 3, a total of 19 studies addressed rates of adherence to oral nonendocrine antineoplastic therapies in samples of patients with various cancer types: 47.4% (n 5 9) chronic myeloid leukemia, 26.3% (n 5 5) mixed cancers, 15.8% (n 5 3) breast cancer, 5.3% (n 5 1) hepatocellular carcinoma, and 5.3% (n 5 1) gastrointestinal cancer. For this group of studies, average rates of adherence ranged from a low of 69% [38] to 100% [39] across a 6-month time period and from 69.6% [40] to 88.2% [41] at 1 year. Threshold scores indicated that as much as 20.5% [42] of patients (per MEMS) and 36.1% [43] of patients (per physician report) met criteria for poor adherence at baseline assessment.…”
Section: Rates Of Adherence To Oral Antineoplastic Therapiesmentioning
confidence: 99%
“…Guérin et al [12] reported that among the patients treated with a second-line TKI, those treated with NILO had a significantly higher adherence compared to patients treated with dasatinib. However, Trivedi et al [13] reported that among second-line TKI-treated CML patients, dasatinib patients had significantly higher adherence and lower discontinuation rates compared with patients receiving second-line NILO. Chen and Wu [14] commented on the results described above.…”
Section: Figmentioning
confidence: 99%